DESIGNING RESILIENT DISTRIBUTED SYSTEMS: FAULT TOLERANCE STRATEGIES AND INSIGHTS - Vedant Agarwal (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Distributed systems are the backbone of modern applications, yet their inherent complexity makes them prone to failures that can disrupt operations and compromise data integrity. This article explores fault tolerance strategies designed to ensure operational reliability, data consistency, and system resilience in distributed environments. Key topics include replication mechanisms, consensus protocols, failure detection, and recovery strategies, each examined through the lens of real-world deployments. The trade-offs between performance, consistency, and availability are analyzed to provide actionable insights for system architects. Emerging trends such as AI-driven monitoring and self-healing systems are also discussed, offering a glimpse into the future of fault tolerance. By integrating these strategies, organizations can build robust distributed systems capable of minimizing downtime, maintaining data reliability, and scaling to meet the demands of modern applications.